Esteban Rodríguez Herrera's didactic approach in his work on grammatical analysis of journalistic text (Islas, 2023)
Introduction: The overall objective of this work is to analyze the normative role of lexicographer Esteban Rodríguez in the grammatical theory of his time, through the analysis of journalistic texts, which demonstrates his didactic vision for the correct use of the language.Methods: Theoretical and empirical methods are used to determine the frequencies of incorrect usages and the didactic treatment to eliminate them.Results: The main errors found in journalistic texts and the ways to eradicate them from the grammatical theory and the appropriate exemplification of them are gathered. Since this text is of an older date, it enriches Rodríguez's (1953) explanations to perfect the didactic purpose of the analyzed work.Conclusions: The study shows how Esteban Rodríguez Herrera integrates lexicographic and grammatical knowledge for didactic purposes. While the analyzed text may not prioritize didactic principles, the linguistic analysis's ultimate goal is evident. The language didactics based on grammatical theory is not far from communicative processes but is linked to comprehension, analysis, and textual construction.
Keywords: lexicographer; grammatical theory; grammar didactics; writing